The Effect of Inclination into Heat Convection Flow of Dissipative Fluid in a Channel of Porous walls - Tagread Shuker (Al-Rafidain Journal of Computer Sciences and Mathematics)
This paper is devoted to the study of the effect of inclination into heat transfer by natural convection of fluid flowing through a channel with porous walls; the model has been created by using two-dimensional Cartesian co-ordinate and the resulting differential equations governing the model solved numerically  in two phases (steady-state and unsteady-state) based on finite difference method.